(untitled) - Shibata, Tsutomu (Washington, D.C., 2006)
These two volumes analyze Japan from the Knowledge Economy (KE) perspective, covering a wide range of sectoral issues in development including the macro economic framework, education and skills training, the national innovation system, science and technology, information and communication technology, and infrastructure. While Volume 1 explores the four pillars of the "Knowledge for Development" framework, the second volume presents up-to-date case studies of outstanding Japanese private companies that each characterize different aspects of KE. By combining economics and business, these volumes allow readers to grasp the full scope of today's knowledge economy.
Keywords: Economic policy,Economic development; Japan,Japan